حوكمة الشركات كإطار لتطور ونمو الشركات العائلية - سفيان, زغوان; الأزهر, عزه (Université de M'sila, 2020)
تهدف دراستنا في هذا البحث إلى إبراز أهمية الحوكمة للشركات العائلية وتحديد مزاياها ومخاطرها وسبل تطبيقها لهذا النوع من المؤسسات الذي يمثل العصب الرئيسي والنواة الأساسية للإقتصاد الجزائري ولأي إقتصاد في العالم. وخلصت الدراسة إلى أن حوكمة الشركات أصبحت حتمية وليس خيار يضمن للشركات العائلية الإستمرارية والنمو ويمنع حدوث حالات التصادم بين أفراد العائلة مهما إختلفت الأجيال، ونظرا لخصوصيات الشركات العائلية يتوجب عليها وضع ممارسات للحوكمة بشكل مرن يتناسب وطبيعتها ويدور حول مجموعة من الهياكل أهمها إجتماع للعائلة للمشاركة في المعلومات ويرافقه جمعية العائلة والتي تجتمع لتبادل الآراء وتطوير المشروع، وأخيرا مجلس العائلة لإدارة القضايا العائلية وحل المشاكل. Our study in this research aims at highlighting the importance of governance for family companies, their advantages and risks, and the ways to apply it to this kind of enterprise, which represents the main pillar and core of the Algerian economy and any economy in the world. the study concluded that corporate governance has become inevitable and not an option that guarantees family businesses continuity and growth and prevents the occurrence of collisions between family members regardless of generations. Given the specificities of family companies, they must develop practices of governance in a flexible manner that is appropriate to their nature and revolves around a range of structures, the most important of which is a family meeting to share information, accompanied by the Family Association, which meets to exchange views and develop the project, and finally the Family Council to manage family issues and solve problems.
Keywords: ح ; كمة الشركات ; الشركات العائلية